THE DEVELOPMENT OF SCIENTIFIC TEACHING MATERIALS BASED ON STEM-PjBL AS A CHANCE TO IMPROVE STUDENT'S CREATIVE THINKING ABILITY ON THE TOPIC OF ANALYZING OF LIGHT AND OPTICS - Putri Ratna Sari; Parno Parno; Sugiyanto Sugiyanto (Jurnal Pembelajaran Sains, 2021)
Teaching material is a learning media that can be employed for independent learning. However, the learning media based on the real problem, assembling STEM aspect, and using independent learning strategy have not much been developed. Based on the observation results in junior high school, students experience the distraction to comprehend the concept of light and optics. The understanding of the concept and language is the principle of creative thinking. Therefore, the purpose of the study is to develop and test the teaching material eligibility based on STEM-PjBL toward light and optics analysis so that it is moderate to improve the students’ creative thinking. This study is a research development using the 4-D model by Thiagarajan that includes several stages; define, design, develop, and disseminate. This study solely reached the development stage. The feasibility test was carried out through validation media, material validation, and practical test. The finding of the research indicated that the teaching material developed is valid and eligible to use.